REVITALISASI NILAI-NILAI KEARIFAN LOKAL BAGI UPAYA RESOLUSI KONFLIK - Suprapto Suprapto (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2013)
The involvement of local wisdom in conflict resolution and peace building is not the only way to resolve conflict. Some level of conflict resolution should be there along the path of conflict resolution. The stressing on the patterns of conflict resolution is still limited on conflict settlement and need to develop toward peace building involving local wisdom which ic proven to be able to maintain social harmony. Considering to the norms had been long internalized among society, the society members strongly held the society order. The most important in this context is the need in the side of the elites to discuss the patters of local wisdom based peace building.